Security Threats and Mitigation Approaches in IoT based Applications - A.P. , Nirmala (International Journal of Psychosocial Rehabilitation, 2020)
The Internet of Things (IoT) as a budding technology has modernized the global network comprising people, smart devices, intelligent objects, information, and data. There is a huge opportunity for IoT to make the world more available, integral, accessible, confidential, interoperable, and scalable. IoT can be exercised in domains such as healthcare, transportation, entertainment, power grids, and smart buildings. IoT is likely to work as a catalyst for future technological innovations, and its use is presumed to grow rapidly. Various devices that we use on a daily basis can connect with each other via the internet; this has been made possible by IoT. There remain security concerns due to the connection of numerous devices to the internet and the massive data associated with it. Protection and integration of heterogeneous smart devices and information communication technologies (ICT) are the significant factors of the paradigm. The security threats that the users face in the environment of IoT and countermeasures to mitigate them are discussed in this paper.